The Embeddedness of Behavior Environmental Health in Waste Management with Flies Density Against the Symptoms of Diarrhea in the Rumbai Pesisir District - Carles Carles; Viktor Amrifo; Zahtamal Zahtamal (Program Pascasarjana Universitas Riau, 2017)
The behavior of the community or individual to manage waste in the sub-urban area of Rumbai Pesisir District are not lead to positive behaviors such as sorting, collection, disposal of garbage into temporary shelters. Public indifference of the garbage will result the degradation of environmental quality that will affect the people life quality, garbage piled will make flies breed thus allowing family members experiencing symptoms of diarrhea. The purposes of this research is to analyze direct and indirect effect between the behavior of waste management with the density of flies on the symptoms of diarrhea. Based on the results, there is the effect of garbage management behavior towards the density of flies, the better the waste management behavior the lower the density of flies on the contrary, if the behavior of waste management to the occurrence of flies is not good than the density of flies increased. There is the influence of the density of flies against diarrhea disease symptoms, the higher the density of flies the symptoms of diarrhea is increasing conversely the lower the density of flies then the lower the incidence of diarrhea symptoms. There is the influence of the simultaneous behavior of waste management and the density of flies against the symptoms of diarrhea, if the behavior of waste management better than the number density of flies will be lower and the symptoms of diarrhea diseases is getting lower on the contrary if the behavior of the waste management worse than the number density of flies higher and symptoms of diarrhea disease more increasing. This research advised to the community, for always maintain the cleanliness of the environment in their house to reduce or eliminate the breeding sites of flies. Additionally the community need to sorting, collection and disposal the garbage into temporary shelters, using the hood of food cover to reduce hazards of food contamination by flies